Mitigating the effect of series capacitance unbalance on the voltage reduction capability of an auxiliary CSI used as switching ripple active filter - Papadopoulos, Savvas; Klumpner, Christian; Rashed, Mohamed; Wheeler, Patrick (2016)
The use of series connected capacitors for high voltage applications has been proven to be beneficial for voltage stress reduction across power semiconductors. In a 3-phase grid any asymmetry in the value of the series capacitance may lead to significant variations in the voltage seen across the low voltage converter. This paper investigates the effects of an unbalanced set of series connected capacitors used to reduce the voltage stress across a three phase current source inverter (CSI) used as an active power filter and proposes a method to minimize the impact of unbalance on CSI voltage ratings. It is shown that through a proposed solution which adjusts the level of inverse sequence current component in the series capacitors, the reduced CSI voltage stress can be maintained for large capacitor unbalance and validated by simulation and experimental results.